FINANCIAL EDUCATION AND FINANCIAL LITERACY ON MICRO ENTREPRENEUR GROWTH IN INDONESIA - Roslita, Evy (ESENSI: Jurnal Manajemen Bisnis, 2023)
Micro, Small, and Medium Entreprises (MSMEs) in Indonesia play an important role in Indonesia's economic growth. The contribution of MSMEs to GDP also reaches 60.5%, and to employment is 96.9% of the total national employment absorption. Therefore, special attention to promoting their financial literacy is needed. It is believed that financial knowledge can make the quality of financial business decisions